A history of knowledge : - Doren, Charles Van (Ballantine, 1991)
Van Doren, once editorial director of the Encyclopedia Brittanica , has produced a miniature encyclopedia, organized to show that there is progress in knowledge. He praises Columbus for giving us "a world well on the way to the unity it experiences today." India is mentioned as the source of the caste system. The Chinese gave us Confucius, but Van Doren notes their main legacy seems to be good recipes for tyranny. He warns that some good knowledge is unpleasant: we must now control our technology. Ultimately, the best knowledge for him is Western scientific knowledge since it is cumulative, meaning that better theories nearly always replace worse ones. An avid reader of Popular Mechanics who went to sleep in Peoria, Illinois in 1920 and awoke today with this book in her/his hands would probably find their ideals intact, needing only new technical knowledge and preparation for Van Doren's predicted revolt of intelligent machines. Van Doren has distilled the ideology of scientific progress into a neat, short drink that should win him a place on every library shelf.